PATTERNS AND AWARENESS OF CODE-MIXING AMONG INDONESIAN YOUTHS IN AN ENGLISH-SPEAKING COMMUNITY: A SOCIOLINGUISTIC ANALYSIS - Alfarras, Riziq Prio; Siwi, Purwanto (Universitas Islam Sumatera Utara, 2025)
This qualitative study investigates the patterns and underlying factors of code-mixing (CM) among Indonesian youths in Aaron's English-Speaking Club, a community dedicated to practicing English in Medan, Indonesia. Employing a grounded theory approach by Charmaz (2016), the research involved in-depth interviews with ten club members, selected via probability sampling. The conversations were analyzed to quantify the frequency of CM (the insertion of Indonesian words into English discourse) and to identify the sociolinguistic factors influencing this phenomenon using the framework of Holmes (1992). Findings reveal that all participants engaged in CM, with percentages ranging from 0.52% to 24.34% of their total words. The analysis indicates that CM is not an indicator of low proficiency but a strategic, communicative resource. Key factors influencing CM included occupation, cultural attitude, and regional background. Notably, participants were initially unaware of the linguistic concepts of CM and code-switching (CS), but upon explanation, all identified more strongly with CM than CS in their typical language use. The study concludes that CM is a natural and prevalent feature of bilingual communication among these youths, reflecting their dynamic linguistic identity and the specific social context of their English practice community. It recommends increased metalinguistic awareness to empower speakers in their bilingual journey.